Goodness, Compassion and Virtue: Keys to Rousseau's Education Proposals - Villar Ezcurra, Alicia (Historia y Memoria de la Educación, 2015)
The defense of the innate goodness of human beings is one of the most wellknown and polemic aspects of J. J. Rousseau’s philosophy. This article analyses the link between his anthropological conception and his educational model. In defending the idea that the human being has a natural «disposition» for doing good, feeling compassion and empathizing with others’ suffering, Rousseau is not invoking some long-lost, savage state of ours; rather, he is referring to a model of education that can help to encourage and develop such qualities by means of «maxims of pity» and the practice of virtue. In doing so he is proposing an education that encourages cooperation as well as humane feelings that will lead individuals to see others as equals rather than as rivals. We also offer a reflection here on the ambivalence of compassion and on some of the assessments and opinions regarding this sentiment, which was considered by Rousseau to lie at the very origin of humane feelings.